The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/etc.1800
|View full text |Cite
|
Sign up to set email alerts
|

Reduced adsorption of propanil to black carbon: Effect of dissolved organic matter loading mode and molecule size

Abstract: In the present study, the reduced adsorption of propanil on black carbon (BC) influenced by dissolved organic matter (DOM) was verified to be closely related to DOM molecule size and loading mode. Two congenetic carbons, a rice-residue-derived BC and the reduced product (RC), were characterized by similar specific surface area and different surface properties. Reduced product exhibits higher adsorption of propanil and DOM than BC. A series of model DOMs, including tannic acid (TA), pentagalloylglucose (PA), 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Moreover, the strong sorption domain (i.e. the micropore system) of the tiny BC fraction in the soils might be blocked or occupied by soil components such as DOC and mineral clays, thus attenuating the possible influence from BC (Kwon and Pignatello, 2005;Brändli et al, 2008;Xiao et al, 2012). Agarwal and Bucheli (2011) also observed the only governor of TOC in the distribution of PAHs in the organic carbon-rich agricultural soils.…”
Section: Effects Of Soil Properties On Extractability Of Pahs In Agedmentioning
confidence: 99%
“…Moreover, the strong sorption domain (i.e. the micropore system) of the tiny BC fraction in the soils might be blocked or occupied by soil components such as DOC and mineral clays, thus attenuating the possible influence from BC (Kwon and Pignatello, 2005;Brändli et al, 2008;Xiao et al, 2012). Agarwal and Bucheli (2011) also observed the only governor of TOC in the distribution of PAHs in the organic carbon-rich agricultural soils.…”
Section: Effects Of Soil Properties On Extractability Of Pahs In Agedmentioning
confidence: 99%
“…This relationship has been demonstrated in other carbon materials [24]. Our simulation results showed that the maximum numbers of water, EG, DMF, and NMP molecules that can be adsorbed per unit cell of GO are 490, 120, 97, and 70, respectively.…”
Section: Relationship Between the Interlayer Spacing Of Go And The Simentioning
confidence: 51%
“…The hydrodynamic diameter of a water molecule is ~ 2.7 Å [25]. The intercalation of a water monolayer causes the lattice of GO to expand by 2.2-2.5 Å [24]. The size of the DMF layer adsorbed by GO structure is ~ 4.4 Å [26].…”
Section: Relationship Between the Interlayer Spacing Of Go And The Simentioning
confidence: 96%
“…After coexisting with 5 mg L −1 TA and GA, the maximum adsorbed capacity (q m ) of MCLR decreased to 92 and 6 %, respectively (Table 6S). This result indicated that TA acted as a strong competitor by occupying the effective adsorption sites for MCLR in the mesopore and macropore regions because of the larger molecule size of TA (1.93 nm×1.73 nm×1.32 nm) than MCLR (Xiao et al 2012). However, GA shows a slight influence on MCLR adsorption because the dominant adsorptive domain for GA is micropore, which is inaccessible to MCLR macromolecules.…”
Section: Effect Of Dommentioning
confidence: 90%
“…The three-dimensional size of MCLR was reported as 1.9 nm×1.5 nm×1.1 nm (Teng et al 2013). Therefore, the micropore regions (pore size <2 nm) may be unavailable for MCLR adsorption because the second widest dimension of MCLR (1.7× 1.5=2.55 nm) is 1.7 times larger than 2 nm (Xiao et al 2012). This notion is supported by evidence that the uptake of MCLR on micropore-based carbon is similar to that on nonporous carbon (Pendleton et al 2001).…”
Section: Characterization Of Biocharsmentioning
confidence: 97%